Biology, Ecology, and Management of Key Sorghum Insect Pests. Issue 1 (18th January 2021) - Okosun, Olabimpe O; Allen, Kerry C; Glover, James P; Reddy, Gadi V P
Abstract: Sorghum, Sorghum bicolor L. Moench (Poaceae), is a highly valued crop cultivated worldwide, with the grain and stover being of equal importance in some developing countries. Sorghum can produce high yields even under adverse environmental conditions, however, damage from insect pests at various stages of the plant's development can reduce its productivity, impacting low-income farmers in developing countries. Important sorghum insect pests include leaf-sucking species, leaf-feeding species, stalk or stem borers, pests of the panicle and of the stored grain. Modern control strategies include cultural controls, biological control, pesticides (chemical, botanicals, or microbial), and host plant resistance. An integrated approach is recommended and based on a combination of insect growth regulators and conservation practices to protect natural enemies at the landscape level. Long-term successful management also requires regulatory policies to limit the invasion of new pests.